O campo da cultura na América-Latina e o caso da Ditadura Militar Brasileira: questões de autonomia, tradição e modernidade - Menezes, Pedro (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
The article intends to analyze the Latin-American cultural field, emphasizing two of its relevant characteristics: 1) its fragile autonomy, characterized by a strong dependence of the arts on both the State and the market, which results not only in the fading of the line that supposedly would divide culture in “high” and “low”, but also in the fusion of these two poles into the same, undistinguished whole; 2) the conflictual harmony between the ideas of tradition and modernity. In order to demonstrate both dynamics, the text brings into focus a case study: the Brazilian military dictatorship period (1964 -1985) and the State-market-artists triangle forged at the time.